Development and Research Status of Heavy Oil Enhanced Oil Recovery. (12th February 2022) - Xue, Liang; Liu, Pengcheng; Zhang, Yun
Abstract : Heavy oil is an important part of petroleum hydrocarbon energy. With the depletion of conventional crude oil reserves, successful and efficient exploitation of heavy oil resources is becoming increasingly important. This article focuses on the nine relatively mature heavy oil development technologies from the perspectives of the level of understanding of the mechanism and the scale of the mining field: steam huff and puff, steam flooding, steam-assisted gravity drainage (SAGD), in situ combustion, thermochemical combined flooding, multicomponent thermal fluid, polymer flooding, chemical viscosity reduction development, and microbial oil recovery, which are divided into two technical categories: thermal recovery and cold recovery development. The basic development principles are explained, and application examples of the two categories of techniques are provided. It is pointed out that thermal compounding, cold mining development, and nanomaterial applications will be the three development trends in heavy oil development.